Analisis Management Resiko pada Perusahaan Emje’s Farm Melon Hidroponik Cianjur - Thalia, Dinda; Sidik, Fajar; Safha, Libbya (Universitas Serambi Mekkah, 2024)
This research explores comprehensive risk management strategies in hydroponic melon cultivation, with a case study on EMJe's Farm. The hydroponic farming sector faces various complex challenges that require a systematic approach to risk mitigation. The research aims to identify, analyze, and evaluate various risks that affect the productivity and sustainability of hydroponic melon farming. The research methodology used both qualitative and quantitative approaches, including field observations, in-depth interviews with management, and analysis of company documents. The research identified four main risk categories: production risk, market risk, technology risk, and environmental risk. Results show that the implementation of structured risk management can reduce potential losses by 60% and improve operational stability. Key research findings include the importance of continuous monitoring systems, diversification of crop varieties, use of advanced technology, and strategies to anticipate market fluctuations. This study makes a significant contribution to understanding the dynamics of risk management in modern hydroponic farming systems, with practical implications for similar agribusiness actors. Research recommendations include the development of integrated risk management protocols, human resource capacity building, and adoption of innovative technologies to minimize uncertainty in hydroponic melon production.